Additions to the orchid flora of Tabasco, Mexico - González-Aguilar, Marlon Aramis; Burelo-Ramos, Carlos Manuel (Instituto de Ecología, A.C., 2017)
Background and Aims: The most recent checklist of the family Orchidaceae for the state of Tabasco recognized 116 species grouped in 60 genera. However, field work was necessary in those sparsely collected and unexplored areas. The goal of this work was to update the list of Orchidaceae of Tabasco from collections of plant material in diverse environments of this state.Methods: In the framework of the project “Systematics and Floristics of the Family Orchidaceae of Tabasco and status of the populations of three species listed in NOM-059-ECOL-2010”, orchids were collected between the years 2014 and 2015 in the entire state, focusing on little explored areas.Key results: 37 species and nine genera are added to the orchid flora of the state, which increases as such to 153 species, one variety and 69 genera. As a consequence, the Orchidaceae is now the third largest angiosperm family in Tabasco, only preceded by Fabaceae and Poaceae.Conclusions: Most of the species are distributed in the mountains of the state near the border with Chiapas and Guatemala, especially in the mountain chain of Huimanguillo. The populations of many of these species are in danger due to livestock and farming in the region, resulting in habitat loss.